ASTRA DAIHATSU CUSTOMER VIRTUAL EVENT’S SPECIAL EVENT STRATEGY BY PT. MAHA KREASI INDONESIA - Jasmine Dewi Nabila; Dimas Satrio Wijaksono (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2021)
The spread of the Covid-19 pandemic in all parts of the world including Indonesia, resulted in most industrial sectors experiencing economic paralysis. Business people must do various ways to keep their business running and marketing activities carried out with innovations according to the situation. With all the limitations of movement, the emergence of various virtual events is a solution for marketing activities to keep going in this critical pandemic. Astra Daihatsu is one of the brands that is active in holding virtual events during the pandemic through PT. Maha Kreasi Indonesia as an alternative to their marketing activities during the pandemic. Customer virtual events are carried out to maintain Astra Daihatsu's communication with the community, and be active in continuing Astra Daihatsu's routine marketing activities, namely holding events. The purpose of this study was to identify the special event strategy implemented by PT. Maha Kreasi Indonesia as the organizer of the Astra Daihatsu virtual event. This study uses the theory of special event stages by Joe Goldblatt which consists of research, design, planning, coordination, and evaluation. The research method used is descriptive qualitative with a post-positivism paradigm and data collection was carried out by in-depth interviews, observative pastoral, documentation, and literature study. The results obtained explain the application of the special event stages in the implementation of the Astra Daihatsu virtual event by PT. Maha Kreasi Indonesia in carrying out its marketing activities.